An empirical study on new product development process by Nonparametric Combination (NPC) testing methodology and post- stratification - Livio Corain; Luigi Salmaso (Statistica, 2007)
This paper explores through an empirical application of NonParametric Combination (NPC) testing methodology, the different behaviours that distinguish those firms that develop successful products from those that are less successful. The NonParametric Combination (NPC) of dependent permutation tests methodology, particularly useful with observational studies and in presence of non-normal and/or categorical data, consists of an innovative testing method that allows the researcher to go beyond some usual parametric testing constraints, such as the multivariate nature of most real problems and the relative small size of the available datasets, when sometimes the number of variables can be greater than the number of available observations.